Paro cardiorrespiratorio hospitalario: un desafío en la actualidad - Sosa Acosta, Luis A.; Carmona Pentón, Carmen R.; Plaín Pazos, Claribel; Aguiar Mota, Carlos A.; Rodríguez Herrera, Elsa; Gómez Acosta, Elba de la C. (CorSalud, 2020)
Paro cardiorrespiratorio hospitalario: un desafío en la actualidad